1998
DOI: 10.1016/s1097-2765(00)80064-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Effects of Trehalose on Protein Folding In Vitro and In Vivo

Abstract: The disaccharide trehalose is produced in large quantities by diverse organisms during a variety of stresses. Trehalose prevents proteins from denaturing at high temperatures in vitro, but its function in stress tolerance in vivo is controversial. We report that trehalose stabilizes proteins in yeast cells during heat shock. Surprisingly, trehalose also suppresses the aggregation of denatured proteins, maintaining them in a partially-folded state from which they can be activated by molecular chaperones. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
475
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(510 citation statements)
references
References 56 publications
30
475
1
4
Order By: Relevance
“…An increasingly wide range of functions are attributed to trehalose; for example, it is well known to act as an organic osmolyte in micro-organisms [17,[37][38][39] and it has also been implicated in the cold stress response of E. coli [15]. Heat shock and oxidative stress do not seem to activate tps genes in A. avenae, but this contrasts with the situation in micro-organisms, where trehalose is thought to play a role [13,14,16]. At present, other than a few studies in anhydrobiosis, there is sparse information on trehalose synthesis in nematodes [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasingly wide range of functions are attributed to trehalose; for example, it is well known to act as an organic osmolyte in micro-organisms [17,[37][38][39] and it has also been implicated in the cold stress response of E. coli [15]. Heat shock and oxidative stress do not seem to activate tps genes in A. avenae, but this contrasts with the situation in micro-organisms, where trehalose is thought to play a role [13,14,16]. At present, other than a few studies in anhydrobiosis, there is sparse information on trehalose synthesis in nematodes [40].…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae), the majority are not; accordingly, in the latter species, the role of trehalose is probably not related to desiccation tolerance. Rather, trehalose might be a general stress molecule, at least in micro-organisms, being linked to multiple stress responses, including those to heat [13,14], cold [15], reactive oxygen species [16] and elevated osmolarity [17].…”
Section: Introductionmentioning
confidence: 99%
“…This might be mediated by one or more of the three STREs (stress-responsive elements) in the promoter region of the NTH1 gene. According to the current model, during heat shock trehalose protects cellular proteins against denaturation and subsequent aggregation, but inhibits the solubilization of protein aggregates and the refolding of the partially denatured proteins during recovery from heat shock [6]. However, it has been unclear [7] whether Nth1 is important because of its role in trehalose hydrolysis or whether Nth1 displays an additional (e.g.…”
Section: Trehalase Activity Correlates With Heat-shock Sensitivity Anmentioning
confidence: 99%
“…This possibility has been supported by recent evidence that high trehalose levels inhibit efficient renaturation of partially unfolded proteins by molecular chaperones like Hsp104 [6]. Although the impaired recovery from heat stress of an nth1∆ mutant is consistent with a requirement for rapid mobilization of trehalose after heat shock, there is no direct evidence that it is the enzymic activity of trehalase, and therefore trehalose mobilization, that is important for heat-stress recovery.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Trehalose, a non-reducing disaccharide, works as an energy source in yeasts, bacteria, fungi, invertebrates, insects and plants. 16,17 Many research demonstrated that the higher trehalose accumulated in the yeast cell the higher tolerance against various environmental stresses, for instance ethanol stress, 18 heat stress, 19 saline stress, 20 and various other environmental stresses. 21,22 In S. cerevisiae, concentration of trehalose is regulated by synthesis enzymes and hydrolysis enzymes.…”
Section: Introductionmentioning
confidence: 99%